1997
DOI: 10.1111/j.1949-8594.1997.tb17376.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer Use and Visualization in Students' Construction of Reflection and Rotation Concepts

Abstract: The effects of a dynamic instructional environment (based on use qfThe Geometer's Sketchpad, N. Jackiw, 1991, in a computer lab) and visualization on eighth-grade students9 fN = 241) construction of the concepts of reflection and rotation were investigated. Also investigated were the effects of the environment on students' two-and three-dimensional visualisation. After controlling for initial differences, it was concluded that students experiencing the dynamic environment significantly outperformed students ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 15 publications
0
23
0
4
Order By: Relevance
“…This result shows that the applications performed by the Computer Group were more successful than the applications as performed by the other two groups. When the literature is examined, many studies are seen to show the result that DGS Cabri is very effective in increasing transformational geometry achievement (Dixon, 1997;Hoyles & Healy, 1997;Kurak, 2009;Yavuzsoy-Köse, 2008;Yazlık, 2011). In this context, it can be said that DGS Cabri is an effective tool for increasing the transformational geometry achievement of teacher candidates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result shows that the applications performed by the Computer Group were more successful than the applications as performed by the other two groups. When the literature is examined, many studies are seen to show the result that DGS Cabri is very effective in increasing transformational geometry achievement (Dixon, 1997;Hoyles & Healy, 1997;Kurak, 2009;Yavuzsoy-Köse, 2008;Yazlık, 2011). In this context, it can be said that DGS Cabri is an effective tool for increasing the transformational geometry achievement of teacher candidates.…”
Section: Discussionmentioning
confidence: 99%
“…For all intents and purposes, different software programs such as GeoGebra or Geometry Sketchpad could have been used instead of Cabri II Plus. Hence, the many other studies that have been performed all found an increase in geometry achievement with software no matter which program was used (Dixon, 1997;Harper, 2002). In the scope of this study, the reason for selecting Cabri II Plus was because the researcher has comprehensive experience with the current software and it has a user-friendly Turkish version with easy-to-use menus.…”
Section: Why Cabri II Plus?mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the literature presents studies in which spatial ability relates to van Hiele levels of geometric thinking, other three-dimensional instruments explicitly integrating mathematical processes should be developed (Del Grande, 1987). Dixon (1997) partly concluded that in her study GSP was not effective in improving students' three-dimensional visualization.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%